Subcellular localization and characterization of nitric oxide synthase(s) in endothelial cells: physiological implications. - Hecker, M (1994)
Endothelial cells (EC) contain a constitutive Ca2+/calmodulin-dependent nitric oxide (NO) synthase (cNOS) which plays an important role in the local control of vascular tone. We compared the subcellular distribution of this enzyme in cultured and freshly isolated pig EC by determination of specific cNOS activity and immunoblot analysis. Similar studies were also performed with cultured and freshly isolated bovine and cultured human EC. Enzyme activity was predominantly (> 70%) associated with the particulate fraction of all EC types tested and was highest in freshly isolated porcine EC. Both specific cNOS activity and immunoreactivity were substantially higher (> 3-fold) in the microsomal as compared with the soluble fraction of all EC types tested. In freshly isolated pig EC, these two fractions also differed in terms of their Ca(2+)-dependency, pH optimum and inhibitor specificity. EC may thus contain either two different cNOS isoenzymes or a single enzyme, the conformation of which differs between the soluble and membrane-bound state. Moreover, detailed subcellular fractionation of freshly isolated pig EC revealed that the distribution of cNOS activity closely resembled that of the plasma membrane marker 5'-nucleotidase, suggesting that most, if not all, of the cNOS activity in these cells is associated with the plasma membrane. This localization might render the enzyme more susceptible to activation by physical stimuli, such as a shear stress-induced change in the fluidity of the plasma membrane. Moreover, the continuous exposure to shear stress in vivo may also upregulate cNOS expression in EC, since specific enzyme activity, immunoreactivity and basal NO release were significantly higher in freshly isolated EC as compared with cultured EC.